Tradisi Tirakatan Bagi Masyarakat Santri Yogyakarta: Studi atas Tradisi Malam Tirakatan dalam Rangka Tujuh Belas Agustus pada Masyarakat Kauman dan Mlangi Yogyakarta - Zunly Nadia (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
The night tradition of tirakatan is not only seen as a tradition of Yogyakarta community routine in order to commemorate the anniversary of Indonesia, but more than that, this night of tirakatan is also loaded with symbols of Javanese society related to Javanese way of life, thought and culture as a whole. Therefore, the night tradition of tirakatan by the people of Yogyakarta this indirectly also shows how the view of life and spirituality of Java community. This paper will show how the meaning of tirakatan for the santri community of Yogyakarta which in this case is the community of Kauman and Mlangi. Based on the results of this qualitative research, there are fundamental differences in the meaning of tirakatan by the two santri in Yogyakarta that is the community of Mlangi and Kauman. This difference of meaning can be seen from several aspects as follows: first, judging from the aspect of modernity. Tirakatan for the kauman community is considered not to have significant benefits for the community in the future. Second seen from the aspect of religion, the two santri also have their own view. For the Mlangi community that the influence of religion is very strong in the implementation of the tradition of the night tirakatan and thus, the implementation of the tradition of tirakatan night is closely related even very identical with religious rituals. While the Kauman community is more meaningful tirakatan as things that are not taught in Islam, so Kauman people tend not to implement tirakatan. Third, seen from the aspect of ancestral cultures, the tradition of tirakatan night is very related to the culture of the ancestors, considering that this tradition is derived from the Javanese tradition. There is also the Kauman community, although very far with the traditions and rituals of the ancestors, but the ideology of ancestors such as harmony, a sense of solidarity is still a very important part in the life of Kauman society.